2015
DOI: 10.1039/c5ra14243a
|View full text |Cite
|
Sign up to set email alerts
|

Endophyte inspired chemical diversity from beta-caryophyllene

Abstract: CommunicationThis journal is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…2). The structure and spectral data of 5 were consistent with a synthetic intermediate in the literature, 25 and therefore it was deduced as a new natural product and named as pestalotiopsin H. Its absolute conguration (1S, 2S, 4S, 5R, 6R, 7R, 8S, 9R, 14S) was identied by single-crystal X-ray crystallographic analysis with a suitable low Flack parameter 0.02 (11) (Fig. 3).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…2). The structure and spectral data of 5 were consistent with a synthetic intermediate in the literature, 25 and therefore it was deduced as a new natural product and named as pestalotiopsin H. Its absolute conguration (1S, 2S, 4S, 5R, 6R, 7R, 8S, 9R, 14S) was identied by single-crystal X-ray crystallographic analysis with a suitable low Flack parameter 0.02 (11) (Fig. 3).…”
Section: Resultssupporting
confidence: 73%
“…It acts as a key precursor in nature to form tricyclic and tetracyclic highly oxygenated caryophyllene-type sesquiterpenes by transannular rearrangements. 11 Its highly oxygenated derivatives were proved to possess signicant bioactivities, including immunosuppressive activity, 7 affecting growth and proliferation of numerous cancer cells, 12 antibacterial activity, 13 and anti-inammatory activity. 14 Although b-caryophyllene is widely distributed, its highly oxygenated derivatives are not common.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is the most expensive method, requiring special operating system security, a large number of configurable factors, and the addition of organic modifiers [ 16 ]. The formation of macrocyclic secondary metabolites during biosynthesis is a thermodynamically beneficial process since a whole series of final biochemical metabolic products can be obtained from one macrocyclic metabolite by transannular cyclization of the macrocyclic structure [ 17 ]. Thus, Zhang et al [ 18 ] showed that alcohol dehydrogenase (IkaC) catalyzes an unusual reaction ( Figure 1 ) of reductive cyclization of compound 1 to ikarugamycin ( 2 ) with the formation of an inner five-membered ring [ 18 ].…”
Section: Natural Macrocyclic Meroterpenoidsmentioning
confidence: 99%
“…Armochaeglobine A ( 223 ) possessed an unprecedented tetracyclic 5/6/7/5 system, while armochaeglobine B ( 224 ) possessed a rare 12-membered cyclic carbon scaffold (Chen et al, 2015a ). Polycyclic compounds with unusual skeletons ( 225 - 231 ) were produced by the endophytic Aspergillus tubingensis KJ-9 through remodeling of the β-caryophyllene skeleton, among which compound 225 featured a novel 5/5/6 sesquiterpene skeleton (Tang et al, 2015 ). Ten new ergosteroids, gloeophyllins A–J, were isolated from the solid cultures of Gloeophyllum abietinum .…”
Section: Terrestrial Microorganismsmentioning
confidence: 99%